Nanoformulated Single‐Stranded RNA‐Based Adjuvant with a Coordinative Amphiphile as an Effective Stabilizer: Inducing Humoral Immune Response by Activation of Antigen‐Presenting Cells. Issue 28 (8th May 2020) - Park, Hyo‐Jung; Bang, Eun‐Kyoung; Hong, Jung Joo; Lee, Sang‐Myeong; Ko, Hae Li; Kwak, Hye Won; Park, Hyelim; Kang, Kyung Won; Kim, Rhoon‐Ho; Ryu, Seung Rok; Kim, Green; Oh, Hanseul; et al.
Abstract: As agonists of TLR7/8, single‐stranded RNAs (ssRNAs) are safe and promising adjuvants that do not cause off‐target effects or innate immune overactivation. However, low stability prevents them from mounting sufficient immune responses. This study evaluates the adjuvant effects of ssRNA derived from the cricket paralysis virus intergenic region internal ribosome entry site, formulated as nanoparticles with a coordinative amphiphile, containing a zinc/dipicolylamine complex moiety as a coordinative phosphate binder, as a stabilizer for RNA‐based adjuvants. The nanoformulated ssRNA adjuvant was resistant to enzymatic degradation in vitro and in vivo, and that with a coordinative amphiphile bearing an oleyl group (CA‐O ) was approximately 100 nm, promoted effective recognition, and improved activation of antigen‐presenting cells, leading to better induction of neutralizing antibodies following single immunization. Hence, CA‐O may increase the efficacy of ssRNA‐based adjuvants, proving useful to meet the urgent need for vaccines during pathogen outbreaks. Abstract : An ssRNA adjuvant formulated with coordinative amphiphiles, bearing a zinc/dipicolylamine complex moiety (Zn/DPA) as a coordinative phosphate binder, promoted effective recognition and antigen‐presenting cell (APC) activation. NP=nanoparticle.